2016
DOI: 10.7860/jcdr/2016/15476.7078
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Retentive Ability and Deformation of Acetal Resin and Cobalt-Chromium Clasps

Abstract: Aim: To compare the retentive ability and deformation of Acetal resin with Cobalt-Chromium clasps via Insertion Removal apparatus after subjecting them to stimulate clinical use. Materials and Methods:Materials used for this study are commercially available Cobalt-Chromium alloy namely Wironit, Bego, Germany and Acetal resin namely Biodentaplast, Bredent, Germany. The test samples were divided into two major groups based on the type of materials used in the study. Each major group is further subdivided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
3
20
1
1
Order By: Relevance
“…Also the results of the present study were at variance with Meenakshi et.al (15) who showed increase in the distance between the tips of the Co-Cr clasps more than that occurred with acetal resin clasps but without significant deformation after 12 months test period.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Also the results of the present study were at variance with Meenakshi et.al (15) who showed increase in the distance between the tips of the Co-Cr clasps more than that occurred with acetal resin clasps but without significant deformation after 12 months test period.…”
Section: Discussionsupporting
confidence: 53%
“…Others reported that the thermoplastic resin direct retainer is more flexible than the conventional Co-Cr direct retainer. (13)(14)(15)(16)(17)(18) There is controversy in the literatures (19)(20)(21)(22) and also little data available regarding the long-term performance of such direct retainers. Therefore this study was aimed to evaluate the fatigue resistance (amount of clasp deformation) of acetal resin clasps and Co-Cr clasps after attachment/detachment cycles on abutment teeth with two different undercuts.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of retention of the clasps due to fatigue resistance test was considered as a good indicator of permanent deformation of the clasps (3) . These agreed with Helal, et al who reported that the clasp may lose its retention force as a result of multiple deflections (12) , and contradict with Meenakshi, et al who showed that the retention force of acetal clasps did not decrease after cycling intervals while the Co-Cr clasps lost retention force within 730 cycles of insertion/removal and continued to lose retention force during the remaining intervals (23) .This may be explained by the method which is used to carry out the test.…”
Section: Discussionsupporting
confidence: 81%
“…To date, the retentive force of a clasp has been reported in many laboratory studies [6][7][8][9][10][11][12][18][19][20][21][22][23][24][25][26]. Ahmad et al [18] mentioned that the mean retentive force for a framework engaging an undercut of 0.25 mm with Akers clasp was 4.77 N. Meenakshi et al [10] showed the clasp required 7.24 N for 0.25 mm undercut and 8.37 N for 0.50 mm undercut. Frank and Nicholls [19] concluded that 300 to 750 g (2.94 to 7.35 N) represented an acceptable amount of retention for a bilateral distal extension RPD.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the measurement of the retentive force of the clasp for RPD, there are also several studies on clasps using the finite element method [ 6 ], on measuring the retentive force using a universal testing machine with a crosshead speed [ 7 ], on weighing the retentive force of removal and insertion cycling of clasp [ 8 ], on cyclic fatigue properties of alloy cast clasps [ 9 ], on an evaluation of retentive ability and deformation [ 10 ], on the comparison of buccal and lingual retention [ 11 ], and on clasps compared with the metal materials used [ 12 ]. These are all studies using large-scale experimental equipment, and until now, there was no equipment in the dental field that could easily measure the retentive force of a clasp of RPD.…”
Section: Introductionmentioning
confidence: 99%